2015
DOI: 10.1111/jorc.12131
|View full text |Cite
|
Sign up to set email alerts
|

Coping in Young People With Chronic Kidney Disease (Ckd)

Abstract: It can be concluded from the interviews that young healthy people and those with CKD alike, utilise a range of coping strategies. The themes derived can prompt researchers to potentially develop a coping measure for a young CKD population. However, a longitudinal study would help to recognise coping strategies young people adopt over time and provide a pathway for the development of a formal coping framework.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 54 publications
0
4
0
Order By: Relevance
“…One study found how young people with ESKD developed problem-focused coping and emotion-focused coping to manage challenging situations in daily life (Muhammad et al, 2016). In our study, one way to cope with school was the possibility to be picked up before the end of the school day as an alternative to being off school on long-term sick leave.…”
Section: Author Manuscriptmentioning
confidence: 70%
“…One study found how young people with ESKD developed problem-focused coping and emotion-focused coping to manage challenging situations in daily life (Muhammad et al, 2016). In our study, one way to cope with school was the possibility to be picked up before the end of the school day as an alternative to being off school on long-term sick leave.…”
Section: Author Manuscriptmentioning
confidence: 70%
“…One study furthermore found that children and adolescents had to accept restrictions to activities, as a result of symptoms, pain and undesirable treatment procedures (Nicholas et al, 2011). However, young people with ESKD also seemed to be able to employ problem-focused and emotion-focused coping strategies and develop resilience (Muhammad, Milford, Carson, Young, & Martin, 2016).…”
Section: Backg Rou N Dmentioning
confidence: 99%
“…2 Coping strategies also have a large role to play living with a LTC, especially for young people with CKD. 4,15…”
Section: According To Article 1 Of the United Nations Convention On Tmentioning
confidence: 99%
“…This relationship would aim to help with understanding, sharing experiences/coping strategies, helping towards autonomy and self-determination. 15 In addition, peer counselling also aids in providing sources of information, advice, support, referral and assistance. Peer counselling is important; it promotes support and mentoring between those who are egalitarian with each other.…”
Section: The Kidney Disease and Renal Support (Kdars) Group For Youngmentioning
confidence: 99%